Comparison of the Detection Rates of Different Diagnostic Methods for Primary Peripheral Lung Cancer - Sun, Lijuan; Qin, Chao; Fu, Qun; Hu, Shuangmin; Zhao, Wenfei; Li, Hongyun (Frontiers in Oncology, 2022)
Objective The present study aims to compare the detection rates of different diagnostic methods for primary peripheral lung cancer (PPLC). Methods The detection rate and patient information were collected from a total of 359 cases of PPLC or a suspected diagnosis of lung cancer; among these, 186 cases were simultaneously treated with fibreoptic bronchoscopy, brush inspection and flush inspection, and 173 cases underwent a computed tomography (CT)-guided percutaneous lung biopsy (PNB). The positive detection rates of the different methods were compared. Results In the detection of peripheral lesions (diameter of <5 cm), the CT-PNB had the significantly highest detection rate, followed by the combined basic method (fibreoptic bronchoscopy + brushing + flushing). The independent use of the three basic sampling methods showed a significantly lower detection rate compared with the combined use. Conclusion In the diagnosis of peripheral lung cancer, the CT-PNB had the best detection rate; hence, it could be used in clinical practice for the diagnosis of such lesions.